1998
DOI: 10.1111/j.1399-0004.1998.tb02745.x
|View full text |Cite
|
Sign up to set email alerts
|

Murine MPS I: insights into the pathogenesis of Hurler syndrome

Abstract: Mucopolysaccharidosis type I (MPS I) is an autosomal recessive disease resulting from deficiency of the lysosomal enzyme α‐L‐iduronidase. A murine model which shows complete deficiency in α‐L‐iduronidase activity has been developed and shows phenotypic features similar to severe MPS I in humans. Here we report on the long‐term clinical, biochemical, and pathological course of MPS I in mice with emphasis on the skeletal and central nervous system (CNS) manifestations. Affected mice show a progressive clinical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
64
0
6

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 34 publications
4
64
0
6
Order By: Relevance
“…Further studies revealed aberrant bone remodeling and growth plate development, and maturation with abnormalities in the early cortical bone structure. 26 In young mice, the growth plate appeared thickened with a high number of chondrocytes, and a disorganized structure was observed in the hypertrophic zone. Arrangement of the primary trabecular bone was abnormal and contained an increased presence of cartilage within the woven bone, suggesting difficulties in cartilage resorption during endochondral ossification.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies revealed aberrant bone remodeling and growth plate development, and maturation with abnormalities in the early cortical bone structure. 26 In young mice, the growth plate appeared thickened with a high number of chondrocytes, and a disorganized structure was observed in the hypertrophic zone. Arrangement of the primary trabecular bone was abnormal and contained an increased presence of cartilage within the woven bone, suggesting difficulties in cartilage resorption during endochondral ossification.…”
Section: Discussionmentioning
confidence: 99%
“…Дефицит фермента α-L-идуронидазы приводит к накоплению гепаран-сульфатов и дерматан-сульфа-тов в тканях ребенка и вызывает поражение различных органов [4]. Заболевание характеризуется задержкой в моторном и умственном развитии, изменением ли-цевого скелета (рис.…”
Section: актуальностьunclassified
“…В слу-чае легкого течения в дебюте заболевания соматиче-ская патология отсутствует или представлена в мяг-кой форме (ограничение подвижности в суставах, частые респираторные заболевания, помутнение ро-говицы, пупочная и/или паховая грыжа) и поражение костно-суставного аппарата часто служит причиной обращения к врачу [5]. По данным реестра мукополи-сахаридоза I типа, более 80% пациентов с синдромами Гурлер-Шейе и Шейе в дебюте заболевания имели контрактуры суставов [7][8][9][10][11].…”
unclassified
“…Рентгенологические проявления поражения опорно-двигательного аппарата при всех типах му-кополисахаридоза получили наименование «множе-ственный дизостоз» [10,11]. Термин включает в себя такие изменения, как аномальные формы позвонков и ребер, широкие лопатообразные ребра, короткие ключицы, увеличенный размер черепа, утолщение диафизов, точечные пястные кости.…”
unclassified